Improved tissue integration of a new elastic intraperitoneal stoma mesh prosthesis. Issue 5 (22nd January 2020) - Eickhoff, Roman; Heise, Daniel; Kroh, Andreas; Helmedag, Marius; Klinge, Uwe; Neumann, Ulf P.; Klink, Christian D.; Lambertz, Andreas
Abstract: Parastomal herniation is a frequent complication in colorectal surgery, occurring with a prevalence of 30–80%. The aim of the study was to create a new intraperitoneal colostoma mesh prosthesis (IPST) with enhanced elastic properties made with thermoplastic polyurethane (TPU) monofilaments. We performed open terminal sigmoid colostomies reinforced with either a 10 cm by 10 cm polyvinylidene fluoride (PVDF) or a new TPU/PVDF composite mesh in a total of 10 minipigs. Colostoma was placed paramedian in the left lower abdomen and IPST meshes were fixed intraperitoneal. After 8 weeks, the animals were euthanized after laparoscopic exploration and specimen were explanted for histological investigations. Implantation of a new IPST‐mesh with enhanced elastic properties was feasible in a minipig model within an observation period of 8 weeks. Immunohistochemically, Collagen I/III ratio as a marker of tissue integration was significantly higher in TPU‐group versus PVDF group (9.4 ± 0.5 vs. 8.1 ± 0.5, p = 0.002) with a significantly lower inflammatory reaction measured by a smaller inner granuloma at mesh–colon interface (17.6 ± 3.3 μm vs. 23 ± 5 μm, p < 0.001). A new TPU/PVDF composite mesh with enhanced elastic properties as IPST was created. Stoma surgery and especially the evaluation of the new stoma mesh prosthesis are feasible with reproducible results in an animal model. Tissue integration expressed by Collagen I/III ratio seems to be improved in comparison to standard‐elastic PVDF‐IPST meshes.